H3K9me3-Dependent Heterochromatin: Barrier to Cell Fate Changes - Becker, Justin S. (Trends Genet, 2015)
Establishing and maintaining cell identity depends upon the proper regulation of gene expression, as specified by transcription factors and reinforced by epigenetic mechanisms. Among the epigenetic mechanisms, heterochromatin formation is critical for the preservation of genome stability and the cell type-specific silencing of genes. The heterochromatin-associated histone mark H3K9me3, although traditionally associated with the noncoding portions of the genome, has emerged as a key player in repressing lineage-inappropriate genes and shielding them from activation by transcription factors. Here we describe the role of H3K9me3 heterochromatin in impeding the reprogramming of cell identity and the mechanisms by which H3K9me3 is reorganized during development and cell fate determination.